2023
DOI: 10.1001/jamaneurol.2023.1542
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Dimethyl Fumarate, Fingolimod, and Ocrelizumab After Natalizumab Cessation

Abstract: ImportanceNatalizumab cessation is associated with a risk of rebound disease activity. It is important to identify the optimal switch disease-modifying therapy strategy after natalizumab to limit the risk of severe relapses.ObjectivesTo compare the effectiveness and persistence of dimethyl fumarate, fingolimod, and ocrelizumab among patients with relapsing-remitting multiple sclerosis (RRMS) who discontinued natalizumab.Design, Setting, and ParticipantsIn this observational cohort study, patient data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…24 Our study showed similar results when comparing RTX/OCR with fingolimod over a longer follow-up period (2.4–4.3 years). 25 Similar outcomes were reported in a large retrospective observational MSBase registry study 25 comparing the effectiveness and treatment discontinuation rates in patients switching from NTZ to dimethyl fumarate, fingolimod, or OCR. Patients on fingolimod had higher ARRs (OR = 4.33; 95% CI = 3.12–6.01), increased risk of disability progression (49%), and higher treatment discontinuation rates (OR = 2.57; 95% CI = 1.74–3.80) compared with OCR.…”
Section: Resultssupporting
confidence: 59%
“…24 Our study showed similar results when comparing RTX/OCR with fingolimod over a longer follow-up period (2.4–4.3 years). 25 Similar outcomes were reported in a large retrospective observational MSBase registry study 25 comparing the effectiveness and treatment discontinuation rates in patients switching from NTZ to dimethyl fumarate, fingolimod, or OCR. Patients on fingolimod had higher ARRs (OR = 4.33; 95% CI = 3.12–6.01), increased risk of disability progression (49%), and higher treatment discontinuation rates (OR = 2.57; 95% CI = 1.74–3.80) compared with OCR.…”
Section: Resultssupporting
confidence: 59%
“…Our study suggests that in patients 50 years and older with nonactive MS, discontinuation of fingolimod and natalizumab significantly increased risk of relapse compared with continuing these treatments. Further studies are needed to identify the best therapeutic strategy: switching to an anti-CD20 therapy as in younger patients or deescalation to an MET. On the contrary, we did not find a higher risk of relapse in the anti-CD20 therapy discontinuation group.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, serological markers of HBV infection were repeatedly negative, as it was HBV DNA, thus allowing us to rule out that the latest episode of DILI was associated with HBV reactivation. As low-dose IVMP (100 mg) is administered as an ancillary drug before ocrelizumab infusion, we cannot exclude that this might have contributed to the DILI event associated with ocrelizumab, also considering the previous history of IVMP-associated DILI (mostly observed in association with other treatments) ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…PML risk (index 3.54 plus previous exposure to immunosuppressive treatment) and patient’s convenience (she needs to travel for almost 3 h to get to the hospital) led to the exclusion of natalizumab, as it was deemed to have a detrimental impact on her quality of life, even if adopting an extended interval dosing. Sphingosine 1-phosphate modulators were also discussed, but their efficacy/safety profile was considered less favorable compared to that of CD20-depleting mAbs ( 18–20 ).…”
Section: Discussionmentioning
confidence: 99%